Job Satisfaction in Kathmandu's Hospitality Industry: Exploring Work Environment, Compensation, and Employee Retention (International Journal of Atharva, 2024)
The paper discusses the job satisfaction of employees in the hospitality industry, relating to star-rated hotels and high-quality restaurants in Kathmandu. In this sector, which faces long hours of work, high labor turnover, and heavy workloads, the present research study has tried to assess the satisfaction of the employees concerning the work environment, compensation, workload, benefits, job security, and professional development opportunities. Data for this descriptive quantitative research design were obtained from 144 employees from various departments, mainly food and beverage service and food production. The findings showed that workers were satisfied with their remuneration and work-life balance, as well as working conditions in general: 87.5% were adequately compensated, and more than 90% considered work in a positive light. However, a few respondents were not satisfied with how workload is managed and adequate benefits. The study concludes by stating that job satisfaction has a pivotal role in minimizing turnover of workers, improving productivity, and increasing commitment among workers, which thus gives the management a legitimate reason to make it a priority in the industry.